2013
DOI: 10.4149/neo_2013_045
|View full text |Cite
|
Sign up to set email alerts
|

Predicting axillary sentinel node status in patients with primary breast cancer.

Abstract: The aim of this study is to determine the combination of characteristics in early breast cancer that could estimate the risk of occurrence of metastatic cells in axillary sentinel lymph node(s). If we were able to reliably predict the presence or absence of axillary sentinel involvement, we could spare a considerable proportion of patients from axillary surgery without compromising therapeutic outcomes of their disease. The study is based on retrospective analysis of medical records of 170 patients diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Reyal et al [ 11 ] reported that molecular subtype approximation, including ER, PR and HER2, is also a determinant of ALN status, and another nomogram was later developed (the Paris model). Additionally, several more models [ 9 , 12 15 ] have been developed to predict ALN status. However, none of these models has been widely accepted by treatment guidelines, and clinical practice has not significantly changed.…”
Section: Discussionmentioning
confidence: 99%
“…Reyal et al [ 11 ] reported that molecular subtype approximation, including ER, PR and HER2, is also a determinant of ALN status, and another nomogram was later developed (the Paris model). Additionally, several more models [ 9 , 12 15 ] have been developed to predict ALN status. However, none of these models has been widely accepted by treatment guidelines, and clinical practice has not significantly changed.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is among the most common cancer worldwide and the second cancer-related cause of death in women 1 . Axillary lymph node (ALN) status is one of the most important prognostic and diagnose factor for disease free survival and overall survival in patients with breast cancer 2 . Accurate preoperative identification of ALN status can provide clinicians with important information about their treatment decisions, such as whether axillary lymph node dissection (ALND) in surgery and postoperative adjuvant therapy are needed 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Axillary lymph node (ALN) status is one of the most important prognostic and diagnose factor for disease free survival and overall survival in patients with breast cancer 2 . Accurate preoperative identification of ALN status can provide clinicians with important information about their treatment decisions, such as whether axillary lymph node dissection (ALND) in surgery and postoperative adjuvant therapy are needed 2 . Currently, the intraoperative ALN status in patients with breast cancer is determined by the sentinel lymph node biopsy (SLNB) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Patient age, tumor size, and the preoperative axilla lymph node status from US are parameters considered prognostic indicators in breast cancer and can also be acquired before surgery. We hypothesized that these characteristics might have added value in predicting the proliferation and invasiveness of IBC when combined with US features.…”
mentioning
confidence: 99%